Antenatal Care Dropout and Associated Factors in Ethiopia: A Systematic Review and Meta-Analysis - Gizaw Sisay; Tsion Mulat (SAGE Publishing, 2023)
Background The prevalence and determinants of antenatal care (ANC) dropout in Ethiopia were studied. However, the results were inconsistent and showed considerable variation. Hence, this meta-analysis aimed at estimating the overall prevalence of ANC dropout and its predictors in Ethiopia. Methods A comprehensive search of published studies was done using different international databases such as such as PubMed, DOJA, Embase, Cochrane Library, Google Scholar, and the institutional repository of Ethiopian universities were used to search for relevant studies. Data were extracted using Microsoft Excel spreadsheet, and exported to STATA v17 for analysis. A random effect model was used to estimate the overall national prevalence of ANC dropout. Fixed effects model were used to compute the pooled adjusted odd ratios (AOR) with the corresponding 95% confidence intervals (CIs). I 2  test was used to assess heterogeneity of the included studies. Egger's tests was used to check for the presence of publication bias. Results A total of 7 studies were included in this systematic review and meta-analysis with 11,839 study participants. The overall pooled prevalence of ANC in Ethiopia was found to be 41.37% (95% CI =35.04, 47.70). Distance from the health care facility (AOR = 2.93, 95% CI = 2.75, 3.11), pregnancy complication signs (AOR = 2.97, 95% CI = 2.77, 3.16), place of residence (AOR =  1.79, 95% CI = 1.31, 2.26), educational level (AOR = 1.79, 95%CI = 1.37, 2.21), and age group (30-49) (AOR = 0.61, 95% CI = 0.45, 0.78) were significantly associated with ANC dropout. Conclusion Based on this review and meta-analysis, 41% of Ethiopian women dropped out of ANC visits before the minimum recommended visit (4 times). Hence, to reduce the number of ANC dropouts, it is important to counsel and educate women during their first prenatal care. Issues of urban-rural disparities and noted hotspot areas for ANC dropout should be given further attention.